Isolation of Salmonella from Frozen Chicken Carcasses Produced by Commercial Companies in Khartoum State, Sudan (Journal of Veterinary Medicine and Animal Production, 2021)
Twenty seven broiler chicken carcasses were purchased from retails outlets in Khartoum State; they were produced by six large scale (LS) and three small scale (SS) companies. Three whole chickens’ carcasses that collected randomly from each company, were used to isolate and compare the prevalence and the count of Salmonella. Results showed that the mean values of Salmonella count in skin samples (crop skin and under wing) of carcasses from LS and SS were 2.143 and 2.056 log10cfu/g and 1.927 and 1.837 log10 cfu/g, respectively. The mean values of total salmonella isolated from breast meat (shallow and deep sampling) of carcasses from LS companies were significantly higher than those from SS (1.931 and 1.731 log10 cfu/g vs. 1.169 and 0.0log10cfu/g). Four serovars of salmonella were isolated with S. tyhimurium as the most prevalent (34.37%) followed by S. typhi (28.125%) and S. enteritidis (21.875%) comaped to S. paratyhi (15.625%). Unexpectedly, the hygienic quality of frozen chicken meat produced by SS companies was significantly higher than that produced by LS companies, whereas the highest Salmonella count in both was found in the skin. These results demonstrated the importance of good hygienic practices and risk analysis both at the farm level and broiler processing plants.